2010
DOI: 10.1155/2010/925635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral, Vaginal, and Transdermal Hormonal Contraception on Serum Levels of Coenzyme Q10, Vitamin E, and Total Antioxidant Activity

Abstract: The use of the transdermal contraceptive patch is associated with greater bioavailability of ethinyl estradiol (EE) compared with contraceptive vaginal ring or oral contraceptives (OC). We compared the influences of three contraceptive methods (OC, vaginal ring, and transdermal patch) on serum levels of coenzyme Q10, α-tocopherol, γ-tocopherol and total antioxidant capacity in premenopausal women. Blood samples from 30 premenopausal women who used hormonal contraception for at least 4 months were collected. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
2
11
1
Order By: Relevance
“…The results of the present study revealed that there was significantly lower levels of serum TAS in users of both oral and injectable hormonal contraceptives when compared with non-contraceptive users. This is in agreement with the study of Palan et al (2010) who reported that hormonal contraceptives deplete antioxidant vitamins and trace elements, as measured by the activity of coenzyme Q 10 , vitamin E and total antioxidant activity [17]. Akinloye et al, 2011 attributed decrease in the serum levels of antioxidant trace elements more specifically to increased use of oral contraceptives [18].…”
Section: Discussionsupporting
confidence: 89%
“…The results of the present study revealed that there was significantly lower levels of serum TAS in users of both oral and injectable hormonal contraceptives when compared with non-contraceptive users. This is in agreement with the study of Palan et al (2010) who reported that hormonal contraceptives deplete antioxidant vitamins and trace elements, as measured by the activity of coenzyme Q 10 , vitamin E and total antioxidant activity [17]. Akinloye et al, 2011 attributed decrease in the serum levels of antioxidant trace elements more specifically to increased use of oral contraceptives [18].…”
Section: Discussionsupporting
confidence: 89%
“…The decrease in alphatocopherol may be due to its consequent consumption in order to counterbalance the negative effects of radicals generated . Similarly decreased total antioxidant status (TAS) has been reported among the contraceptive users by Palan et al (2010). The findings of this research are in accordance with the work of Akinloye et al, (2011) who reported deficient trace elements and vitamins among the contraceptive users.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of association between other types of hormonal contraceptive and vitamin A deficiency in the present study might be explained by differences in ovarian hormone concentrations resulting from the type of hormonal contraceptive used . For example, Palan et al . found that oral contraceptive pills produced the highest variation in serum exogenous ovarian hormone concentration, probably due to daily dosing.…”
Section: Discussioncontrasting
confidence: 59%